EKUITAS MEREK (BRAND EQUITY) DAN PENGARUHNYA TERHADAP LOYALITAS PELANGGAN - N P, Maria Goretti Wi Endang (FIA UB, 2007)
This paper tries ti describe and to analize a correlation of brand equity to customer loyality. Brand equity has five dimensions that can not be resparated one another. There are brand awareness, brand loyalty, perceived quality, brand association and anotherbrand asset. Basically, brand has several goals, i.e as company identity, promotion tools, brandimage and market control. In order to get a high customer loyality, produsen must create a product having hard brand equity. In general, a customer who has been trusting with some products, will not change theri buy ability directly although there are many alternative brands giving better quality. For saving that condition, an enterpreneur must increase their product quality and socialize their brand equity product continually